Pełnomocnictwo w Ordynacji podatkowej – nowe regulacje prawne - Łoboda, Marcin (Kwartalnik Prawa Podatkowego, 2015)
Openess of existing legislation concerning power of attorney forced the need to use judicial decisions and commentaries in the process of its application, which is particularly troublesome for the protection of taxpayers’ rights and the need to maintain the balance between public interest and the interests of the taxpayer. Comprehensive regulation of this institution introduced by the Act of 10 September 2015 is of fundamental importance for acting on someone else’s behalf in the sphere of legal relations, to which the Tax Ordinance applies and is an expression of a modern codification of the general tax law. In addition to the special (specific) power of attorney authorizing to act in a given case, which reflects existing regulations, the legislator introduced the institution of a general power of attorney, which is based on existing case law and has functioned for a long time in practice. Flawlessly functioning database containing information on general PoAa, on the one hand is an essential element of professional and efficient tax administration, on the other facilitation for professional representatives. The last type of power of attorney recently implemented to the Tax Ordinance is a power of attorney for the delivery, the establishment of which is the responsibility of the party of the proceedings in certain situations specified in the law. Those regulations are effective from 1 January 2016 while some provisions on the general power of attorney entered into force on 1 July 2016.